Do the extent and direction of arterial remodelling predict subsequent progression of coronary atherosclerosis? A serial intravascular ultrasound study. Issue 5 (10th December 2007) - Sipahi, I; Tuzcu, E M; Moon, K-W; Nicholls, S J; Schoenhagen, P; Zhitnik, J; Crowe, T D; Kapadia, S; Nissen, S E
Abstract : Objective: Despite the link between positive coronary remodelling and acute ischaemic events, no data exist about the impact of arterial remodelling on subsequent progression of coronary atherosclerosis. The objective of this study was to examine whether extent and direction of arterial remodelling are predictors of progression of coronary atherosclerosis. Design, setting and patients: From the Reversal of Atherosclerosis with Aggressive Lipid Lowering (REVERSAL) trial, 210 focal coronary lesions (single lesion per patient) were identified with ⩽50% angiographic diameter stenosis at baseline intravascular ultrasound (IVUS). Remodelling was categorised using the remodelling index. Main outcome measures: Lesion sites were matched to the 18-month follow-up IVUS examination and change in atheroma area was calculated. Additionally, change in atheroma volume of the whole imaged artery was calculated. Results: There were no relationships between baseline remodelling index and change in atheroma area at the lesion site (r = 0.004, p = 0.96) or change in atheroma volume in the whole artery (r = 0.06, p = 0.37). Change in atheroma area was not significantly different in lesions with positive, negative or no remodelling at baseline (0.4 (SD 2.1) vs 0.7 (SD 1.7) vs 0.6 (SD 1.8) mm 2, p = 0.76). Similarly, change in atheroma volume in the whole artery was not significantly different among the three remodelling categories (2.2 (SD 25.0) vs 1.4 (SD 31.2) vs 2.4 (SD 27.1) mm 3, p = 0.98). Conclusions: Extent and direction of arterial remodelling do not predict subsequent progression of coronary atherosclerosis. Although positively remodelled lesions are associated with unstable clinical presentation, they are not associated with accelerated progression of atherosclerosis during lipid lowering therapy.